(untitled) (Philological Studies, 2019)
The article deals with the content peculiarities of the Russian texts generated by the Komi-Permyak bilinguals. While the first contacts of Komi-Permyaks and Russians took place over 500 years ago, until now the influence of the languages and cultures on each other is sufficiently strong. The researched material is the culturally significant referential situations which are pointed by the Komi-Permyaks in the Russian language spontaneous narratives (stories about themselves). The analysis of culturally significant referential situations in texts represents the biculturalism of Komi-Permyaks and demonstrates that now the national identity of Komi-Permyaks is connected with their natural language (KomiPermyak) and the place of residence of the most Komi-Permyaks – the KomiPermyak National District, native nature and habitual rural lifestyles.